Characteristics and Constraints of Pigs Breeding in Sub-Humid Zone of Benin - ADOUKONOU-SAGBADJA, Hubert (My University, 2017)
The purpose of this study was to determine the characteristics and constraints of pig breeding in Benin. Transversal and retrospective survey was used to collect the data on 210 pig farms in seven departments. Breeding was chosen according to the access to the pigsty and availability of breeder to collaborate at the time of data collection. A structured questionnaire was used. The results showed that the average of area at soil of livestock building was higher (117 m2) in Zou. The density of animals was higher in Mono, Ouémé and Atlantique with one animal/m2. Local materials were widely used in infrastructures of pig breeding. Total cloistering (49.43%), seasonal cloistering (41.86%) and total divagation (8.71%) were the breeding methods used. Feeding is based on the use of food residues and domestic processing (52.82%), agricultural by-products (40.78%), agroindustrial by-products (27.14%), provender (10.57%) and fodders. The pigs were exploited primarily for sale but also for ceremonies (28.43%), parties (15.14%) and the gift (7.71%). The constraints to pig’s production were lack of capital, sanitary pressure, food deficit, inappropriate housing, slack, theft and absence of appropriate supervisory structures. Implementation of palliative measures against these constraints is essential for the development of pig production in Benin
Keywords: Feeding; Housing; Pathologies; Pigs breeding; Treatment